Contribuição ao estudo químico de plantas tóxicas do Semiárido: Crotalaria vitelina Ker Gawl e Ipomoea philomega (Vell.) House - Bezerra, Denise Aline Casimiro (2013)
The poisonous plants to livestock research has been restricted only the identification of poison species, epidemiology and clinical signs. But the active principle of toxic plants are little known and its knowledge its very important to develop preventive methods to poisoning which are responsible by countless cattle deaths. This work aimed the contribution to knowledge of active principle these plants, Crotalaria vitellina Ker Gawl (Fabaceae) e Ipomoea philomega (Vell.) House (Convolvulaceae). This work aimed the contribution to knowledge of active principle these plants, Crotalaria and Ipomoea were submitted to phytochemical study for the isolation of its chemical constituents by cromatographic methods followed by its identification through spectroscopic techniques such as Infrared (IR), one and two-dimentional Nuclear Magnetic Resonance (NMR) of 1H and 13C, and Mass Spectrometry (MS) besides literature data. The phytochemical study of C. vitellina resulted on the isolation of the pyrrolizidine alkaloid (type otonecine) named crotavitelin (Cv-1), and were obtained from the crude extract of its fruits, described by first time in the literature. This substance was subjected to acute toxicological evaluation according to OECD Guide 423 (Guideline for Testing of Chemicals), in mice (males and females) orally exposed to 50 and 300 mg/Kg doses and showed a low toxicity on the parameters evaluated. However, histopatologic studies should be performed to investigate the possible toxic effects in celular and tissue levels. Ipomoea philomega was submitted also to phytochemical studies and were isolated eight compounds from the dicloromethane phase of the ethanolic crude extract of the leaves: lanosterol (Ip-1), caffeic acid (Ip-2), ethyl p-coumarate (Ip-3), lupeol (Ip-4), ethyl caffeate (Ip-5), umbelliferone (Ip-6), scopoletin (Ip-7), and the 1,2-benzopirone (Ip-8), has been described for first time in I. philomega.